Model-based control approach for a CPAP-device considering patient's breathing effort. Issue 1 (July 2017) - Scheel, M.; Schauer, T.; Berndt, A.; Simanski, O.
Abstract: The CPAP-therapy is the most common therapy to treat the obstructive sleep apnoea syndrome. Due to a continuous positive airway pressure the upper respiratory tracts are splinted. The internal closed-loop pressure control of the device is more or less disturbed by the patient's breathing. It has been shown that many CPAP-device cannot maintain the reference pressure. This can lead to an unpleasant perception for the patient and cannot always guarantee the success of this therapy. In this work the closed-loop control is improved by a model-based control approach. Therefore, a model for the pneumatic part of the CPAP-device and the patient is introduced. The patient's breathing effort is estimated using a disturbance observer and is used in an extended control strategy.